Understanding experiences of Taiwanese young adults’ compensatory consumption in food - Chen, Pin-Ru (2016)
Food market has become more competitive in Taiwanese industry. The culture of “little happiness”, which has been advocated in Taiwan, strongly relates to compensatory consumption. The purpose of this research is to explore the experiences of Taiwanese young adults’ compensatory consumption in food. This research focused on motivations, emotions and self-esteem behind this behaviour. In-depth interviews were conducted with 14 Taiwanese young adults, who had experienced compensatory food consumption. Data were analysed using thematic analysis.